The independent and coupled effects of feedstock characteristics and reaction conditions on biocrude production by hydrothermal liquefaction. (1st February 2019) - Hietala, David C.; Godwin, Casey M.; Cardinale, Bradley J.; Savage, Phillip E.
Highlights: Probed effects of algae properties and reaction conditions on biocrude production. Measured biocrude yield, elemental content and recoveries, and fatty acid recovery. Numerous effects of concentration and species identity quantified for first time. High-lipid, 30 g L rxn - 1 slurries at 300 °C, 3.2 min produced best biocrude traits. High recovery of unsaturated fatty acids in biocrude achieved at 300 °C, 3.2 min. Abstract: We examined the independent and coupled effects of temperature (150–350 °C), reaction time (1–100 min), slurry concentration (30 and 120 g L rxn - 1 ), biochemical composition (5.2–28.5 wt% lipid, 14.7–50.9 wt% protein), and species identity ( Nannochloropsis, Chlorella, and Spirulina ) on the yield and composition of biocrude oil produced by hydrothermal liquefaction. Measured properties included gravimetric yield, elemental (C, H, N, S, O, and P) composition and recovery, higher-heating value and energy recovery, and fatty-acid profile, content, and recovery. All examined factors affect the yield and composition of the biocrude, with biochemical composition and temperature exhibiting the greatest impacts. We probed the effects of slurry concentration and species identity over numerous combinations of temperature, reaction time, and biochemical composition that were previously unexamined, demonstrating the effects of both slurry concentration and species identity to be of the same order of magnitude as reaction time. Increased slurry concentration appears to promote Maillard reactions that result in increased biocrude yield, C content, and N content and decreased O content. Moreover, the extent of these Maillard reactions may be affected by the ratio of proteins to carbohydrates, with carbohydrates serving as the limiting reactant. High-lipid, 30 g L rxn - 1 slurries reacted at 300 °C for 3.2 min (including 1 min heat-up) generally yielded more biocrude with higher C and H content and lower N, S, and O content than did their high-protein, 120 g L rxn - 1, 200 °C, or 31.6 min counterparts. This condition also provided recoveries of saturated, monounsaturated, and polyunsaturated fatty acids in the biocrude of up to 89.3, 80.1, and 64.7 wt%, respectively, demonstrating for the first time that fast hydrothermal liquefaction can be an effective means of recovering high-value unsaturated fatty acids. The results and expansive experimental data herein provide a deeper level of understanding for microalgal hydrothermal liquefaction, enabling a greater extent of reaction engineering for the process than previously possible.